Novel use of cangrelor in pediatrics: A pilot cohort study demonstrating use in ventricular assist devices. Issue 1 (19th August 2020) - Fahnhorst, Sarah E.; Beasley, Gary; Goldberg, Jason F.; Martinez, Hugo R.; Ryan, Kaitlin A.; Towbin, Jeffrey A.; Boston, Umar; Absi, Mohammed
Abstract: Thromboembolic events and bleeding are major sources of morbidity among pediatric patients supported on a ventricular assist device (VAD). Pharmacokinetics and pharmacodynamics of enteral antiplatelet agents are affected and variable due to erratic enteral absorption in end‐stage heart failure and VAD circulation. Additionally, 20%‐40% of the population are poor metabolizers of clopidogrel, a prodrug, making cangrelor an alternative when antiplatelet therapy is crucial. Cangrelor has been used effectively and safely for short durations in adults during percutaneous coronary interventions, but the use of cangrelor is still under investigation in pediatrics. This case series utilized cangrelor, a novel short‐acting, reversible, intravenous P2Y12 platelet inhibitor in managing pediatric patients supported with a VAD. We performed a retrospective, single‐center review of patients admitted to a tertiary medical center with end‐stage heart failure requiring mechanical circulatory support and concomitant cangrelor administration between January 2019 and March 2020. Platelet function testing, cangrelor dose, bleeding complications, thromboembolic events, and frequency of circuit interventions during the use of cangrelor were recorded. Optimal platelet reactivity, defined as P2Y12 < 180 platelet reaction units (PRU), was measured with serial point‐of‐care testing (VerifyNow). Seven patients, median age of 4.9 years, met the above criteria. Three patients had a diagnosis of complex congenital heart disease. Four patients had dilated or restrictive cardiomyopathy. All patients were on continuous flow VADs. The median VAD duration was 84.5 days (IQR 61.5‐103). The median duration on cangrelor was 43 days (IQR 8‐70). The median cangrelor dose to reach the therapeutic threshold was 0.75 μg/kg/min with the mean P2Y12, while on cangrelor of 164.75 PRU. Bleeding complications included mild gastrointestinal bleeding and hematuria. There was one patient with pump thrombosis requiring intervention. There were no cerebrovascular events while on cangrelor. We report the first successful long‐term use of cangrelor in pediatric patients. The reversibility and short half‐life of cangrelor make it a feasible antiplatelet agent in selected patients. This data supports the use of cangrelor in children as a viable antiplatelet option; with minimal bleeding complications and no cerebrovascular events demonstrated in this cohort.